Intensitas Penggunaan Media Sosial terhadap Body Dissatisfaction pada Mahasiswa Perempuan - Potabuga, Ghia Erisyahria (Institut Agama Islam Negeri Parepare, 2025)
This study aims to analyze the influence of the intensity of Instagram social media use on body dissatisfaction in female students at the Faculty of Law, class of 2023, Sam Ratulangi University, Manado. This study uses a quantitative research method with simple linear regression analysis. The poopulation in this study amounted to 365 students with a sample of 102 female students with a vulnerable age of 18-25 years. The instruments used in this study are the Instagram Social Media Usage Intensity scale compiled by researchers based on the theory of Ajzen and the Body Dissatisfaction scale developed by Cooper, Taylor & Fairburn. The results of the data analysis obtained showed that there was a positive correlation between the intensity of Instagram social media use and body dissatisfaction with a score of 0.410 with a significance value of ρ = 0.000 < 0.005. This means that the higher the use of Instagram social media, the higher the level of body dissatisfaction that occurs in female students. Furthermore, in this study, the behavior of the intensity of Instagram social media use had an influence on body dissatisfaction by 16.8%.